Causative Organisms and their Sensitivity Patterns in Urinary Tract Infection in Children - Dass, Deve; Chohan, Muhammad Nadeem; Talreja, Srichand (Journal of Liaquat University of Medical & Health Sciences, 2019)
OBJECTIVE: To determine causative organisms and their sensitivity patterns in urinary tract infection in children, attending Pediatric Department Dow University Karachi. METHODOLOGY: This Cross sectional study was conducted at pediatric Department, Civil Hospital Karachi from July to December 2014. A total of 150 children between age 1 month to 15 years having the probable Urinary Tract Infection, attending the Pediatric OPD or admitted to ward were enrolled. Urine Culture and Sensitivity sample was collected aseptically. In infants and younger children’s, it was collected by urethral catheterization and in older children collected by mid-stream clean catch void, after proper local cleaning, while in young infant collected by suprapubic bladder aspiration. RESULTS: Among a total of 150 children, mean age of participants was 4.4±3.4 years, 70.7% were above five years of age, 52% were males with male to female ratio were 1.1:1. Urine culture was positive in 29.3% cases, among them 55% were positive for E. coli, 18% for Pseudomonas, 16% for Proteus and 11% for Klebsiella. 70.8% E. coli were not sensitive to amoxicillin and ampicillin. 75% pseudomonas was resistant to ampicillin and amoxicillin.There was no difference in in-vitro and in-vivo response of E. coli to ampicillin and amoxicillin. CONCLUSION: It is concluded from this study that most common organism in Pediatric UTI was E. coli especially in 1-5 years’ age group and most of it were resistant to amoxicillin and ampicillin.